ANALYSIS OF THE IMPLEMENTATION OF FINANCIAL STATEMENT PREPARATION AT MTS.ALWASLIYAH KUALA SILO BESTARI CITY OF TANJUNG BALAI BASED ON INTERPRETATION OF FINANCIAL ACCOUNTING STANDARDS (ISAK 35) - Rizky, Sri; Wahyuni Lubis, Arnida; Samri Juliati Nst, Yenni (JURNAL EKBIS, 2024)
Applying principles to madrasa financial management accounting is one way to make madrasas clean, independent and free from acts of corruption and can improve the development and welfare of the madrasa itself. Financial management based on the Interpretation of Financial Accounting Standards (ISAK 35) is to assist in the preparation of financial reports with a non-profit identity so that the financial report results meet the information needs of financial report users. The aim of this research is to find out whether Mts. S. Alwashliyah Kuala Silo Bestari Tanjung Balai City has implemented reports in accordance with ISAK 35. This research technique is qualitative. The data collection techniques used were interviews, observation and documentation. The data analysis method was carried out using descriptive qualitative, namely data reduction, data presentation and conclusions. The results of this research explain that Mts. S. Alwashliyah Kuala Silo Bestari Tanjung Balai City has not implemented the Interpretation of Financial Accounting Standards (ISAK) 35 which should be carried out by non-profit oriented entities. The recording carried out is still very simple, only reporting cash in and cash out. Because of this, improvements were made to the financial reports in accordance with the provisions of ISAK 35.